Comparative Analysis of Adoption of Improved Dairy-animal Feeding Practices in Assured and Less Irrigated Areas of Uttar Pradesh (Indian Journal of Extension Education, 2012)
Dairying in India has made significant progress and produces of 88 million tonnes of milk. To boost milk production, animal nutritional research interventions to harness the existing genetic production potential optimally of our livestock is essential. Crop residues, roughages, non-conventional feeds and agricultural and agro industrial by-products will continue to be the major inputs as livestock feed for the ruminants. Unfortunately, the existing technologies for improving digestibility of straws have not been used by the farmers. The need is to use biotechnological techniques to develop the recombinant microbes to digest straws and make available energy for livestock feeding. The study was conducted in Aligarh district of Uttar Pradesh with 300 farmers. Majority (52.0 and 81.33%) of the farmers in assured irrigated and less irrigated area adopted the improved feeding practices to a medium level, respectively.